Survival of Human Spermatozoa After Cryopreservation with No-Wash Procedure - Gapon, Ganna O.; Yurchuk, Taisiia O.; Pavlovich, Olena V.; Piniaev, Volodymyr I.; Petrushko, Marina P. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 171